2015
DOI: 10.1007/s10948-015-3188-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Study of Structural and Magnetic Properties of Magnesium-Substituted Nickel–Zinc Ferrites Synthesized by Solid-State and Sol–Gel Routes

Abstract: A series of magnesium-doped Ni 0.65−x Mg x Zn 0.35 Fe 2 O 4 (x = 0.00, 0.04, 0.08, 0.10, 0.12, 0.16) ferrites have been synthesized using sol-gel and solid-state techniques. Sol-gel-synthesized ferrites were sintered at 1000 • C/2 h whereas solid-state-prepared ferrites were sintered at 1250 • C/2 h. X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) studies confirm the spinel phase, and cation ion distribution has been estimated for both the batches using these studies. Magnetic measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…For instance, it was reported that the substitution of Al 3+ in the Ni 0.75 Zn 0.25 Fe 2− x Al x O 4 system led to a decrease in the saturation magnetization ( M s ) from 65.40 to 6.75 emu/g, and the replacement of Ni 2+ by Co 2+ increased the M s value from 75.9 emu/g for Ni 0.5 Zn 0.5 Fe 2 O 4 to 80.6 emu/g for Ni 0.25 Co 0.25 Zn 0.5 Fe 2 O 4 . It was also reported that the doping of Cd 2+ , Cr 3+ , Mn 3+ , Ca 2+ , and Mg 2+ , affected Ni–Zn ferrites in the same way as Al 3+ doping . In addition, some cations such as V 5+ and Cu 2+ doped into Ni‐Zn ferrites could form a liquid‐phase during sintering owing to their low melting point …”
Section: Introductionmentioning
confidence: 94%
“…For instance, it was reported that the substitution of Al 3+ in the Ni 0.75 Zn 0.25 Fe 2− x Al x O 4 system led to a decrease in the saturation magnetization ( M s ) from 65.40 to 6.75 emu/g, and the replacement of Ni 2+ by Co 2+ increased the M s value from 75.9 emu/g for Ni 0.5 Zn 0.5 Fe 2 O 4 to 80.6 emu/g for Ni 0.25 Co 0.25 Zn 0.5 Fe 2 O 4 . It was also reported that the doping of Cd 2+ , Cr 3+ , Mn 3+ , Ca 2+ , and Mg 2+ , affected Ni–Zn ferrites in the same way as Al 3+ doping . In addition, some cations such as V 5+ and Cu 2+ doped into Ni‐Zn ferrites could form a liquid‐phase during sintering owing to their low melting point …”
Section: Introductionmentioning
confidence: 94%
“…[10][11][12] Magnetic properties of ferrite synthesized by different types of sol-gel method were investigated and compared to ferrite produced by conventional ceramic methods. [13][14][15][16][17][18][19] It results that ferrites which exhibit approximately the same permeability and coercive field are achieved by both sol-gel and solid-state methods. However, the magnetic performances at high frequency are not presented in these papers so it is difficult to know if this process is well-adapted to the production of low-loss ferrite.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it exhibits higher mechanical strength, lower coercive force, and favourable chemical steadiness [6]. It has been widely employed in a variety of components for use at high frequencies, such as transformers, inductors, multilayer chip inductors, and modern communication [7].…”
Section: Introductionmentioning
confidence: 99%